Presence of Fatty‐Acid Ethyl Esters in Krill Oil Dietary Supplements. Issue 7 (23rd September 2018) - Srigley, Cynthia T.; Orr‐Tokle, Isa C.
Abstract: Krill oil dietary supplements are increasingly used for their high concentrations of phospholipids (PL), which offer reportedly greater bioavailability of n‐3 polyunsaturated fatty acids (PUFA) than those of triacylglycerols or fatty‐acid ethyl esters (FAEE) commonly found in fish oils and fish‐oil concentrates. This work evaluated the lipid composition of 22 commercial krill oil (CKO) supplements available in the US market, and found ten products (i.e. 45%) contained significant amounts of FAEE, varying from 41% to 75%, by weight. These concentrations of FAEE differed from the minor abundances of FAEE (<3%, by weight) found in manufacturer‐supplied krill oil. The potential clinical and regulatory implications for these findings warrant further investigation.